Phenology (Flowering and Fruiting) of Ten Woody Plants in Linares, North-Eastern Mexico - Rodriguez, Humberto Gonzalez; Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2015)
The present study was undertaken to determine flowering and fruiting phenology of 12 woody species in Linares, Northeast of Mexico during the period from March to December 2013. The most representative species are: Prosopis laevigata (Humb. and Bonpl ex Willd.). M.C Johnst, Ebenopsis ebano (Berland.) Barneby and J.W Grimes, Acacia amentacea D.C., Castela erecta Turpin sub sp texana (Torr. and A. Gray) Cronquist, Celtis pallida Torr., Parkinsonia texana var. Macra (IM Johnst.) Isely, Forestiera angustifolia Torr., Cordia boissieri A.DC., Leucophyllum frutescens (Berland.) IM Johnst., Guaiacum angustifolium Engelm., Cylindropuntia leptocaulis (DC.) F.M Knuth, Opuntia spp, Zanthoxylum fagara Sarg., Sideroxylon celastrinum (Kunth) T.D. Penn, Helietta parvifolia (A. Gray ex Hemsl) Benth., among others. The species were selected on the basis of ecological and nutritional value for livestock and wild ruminant animals and multiple uses of shrubs. There exist a large variability in the phenological stages among species. The first study was concentrated on the basis of the percentage of different phenological stages. The second study was mainly concentrated on the time of appearance of each phenological stage in individual species. The results clearly demonstrate about the variation in phenological time schedule among different species. Very little studies have been undertaken in this aspect in the literature. Therefore, there is a need to evaluate the phenology of each individual species. This knowledge will help forest managers for efficient management of the forest as well as the time of seed production of the species of seeds.